Russian missiles and the European Sky Shield Initiative: German plans to strengthen air and missile defence in the current threat environment - Lydia Wachs (Stiftung Wissenschaft und Politik (SWP), 2023)
Against the background of the Russian missile strikes against Ukraine, Germany has launched the European Sky Shield Initiative (ESSI) to strengthen Europe's air and missile defence. In the short term, it seems there is little likelihood of a Russian missile attack against NATO as Moscow probably lacks both the military means and the incentives. But, in the medium to long term, improving air and missile defence in Europe could curb Russia's coercive power vis-à-vis NATO and thereby strengthen the cohesion of the alliance. However, for this to happen and for the full potential of the initiative to be realized, several strategic, technical-operational and political issues should be addressed. Otherwise, ESSI could end up contributing to NATO fragmentation at the political and technical level.
Keywords: 320; European Sky Shield Initiative; ESSI; European air and missile defence; Nato; Russia; war against Ukraine; long-range weapons; cruise missiles; ballistic missiles; Iris-T SLM; Patriot; Arrow